Enhancement of photoluminescence emission and anomalous photoconductivity properties of Fe3O4@SiO2 core–shell microspheres. Issue 47 (27th May 2015) - Jana, S. K.; Majumder, S.; Satpati, B.; Mishra, S. K.; Srivastava, R. K.; Banerjee, S.
<x xml:space="preserve">Abstract</x> We report the successful synthesis of both pristine Fe3O4 and the Fe3O4@SiO2 core@shell structure. The Fe3O4@SiO2 core@shell sample shows enhanced photoluminescence compared to pristine Fe3O4, while reduced and negative photoconductivity is observed in the same sample.